Mandatory non-financial reporting in the banking industry: assessing reporting quality and determinants - Philipp Schröder (Cogent Business & Management, 2022)
European companies that are larger than a specific size have had to comply with reporting requirements on non-financial topics since 2017 under the European Union's Non-Financial Reporting Directive (2014/95/EU), thereby making non-financial reporting (NFR) mandatory. To the best of the author's knowledge, no study has examined the quality of non-financial reporting in banks' compulsory reports over several years. Therefore, the unique objective of this study is to assess the non-financial reporting quality (NFRQ) in the mandatory NFR of the 100 largest banks operating in Germany over three years, and identify reporting-level determinants (experience, format, framework, and audit) that impact NFRQ. A novel framework is developed to measure NFRQ, and different statistical analyses are used to test hypotheses. This study provides notable results: (1) NFRQ in banks' mandatory reporting is below average despite displaying significant positive development over the years; and (2) banks' NFRQ is significantly impacted by three reporting-level determinants (experience, format, and framework). Additionally, this study highlights meaningful implications for theory, practice, and policy on the future of mandatory NFR in the EU.
Keywords: 650; Germany; banks; corporate social responsibility (CSR); Directive 2014/95/EU; mandatory; non-financial reporting; reporting quality